Systematic Review and Mapping of Theses in the Management of Islamic Education Program Based on Ontological, Epistemological, and Axiological Studies - Yaqien, Nurul; Hasanah, Siti Ma'rifatul; Uyun, Fitratul (J-MPI (Jurnal Manajemen Pendidikan Islam), 2024)
This research aims to systematically review and map theses within the Islamic education management program at State Islamic University of Maulana Malik Ibrahim Malang focusing on study of ontological, epistemological and axiological conducted from 2015 to 2018. The study utilized a combination of Systematic Mapping (SM) and Systematic Literature Review (SLR) methodologies. The research categorizes the structural elements of published theses based on various criteria, including the trends, methodologies, specific emphasis on the integration Islamic principles into education management practices. The analysis revealed the following findings: The results highlight significant trends, revealing the predominant themes in theses research, a total of 263 theses were analyzed, covering 14 themes. Ontologically, this review and capture the Islamic principle shape the understanding of thesis themes. These themes were examined through the lens of educational management theory and Islamic principles, resulting in a scientific integration between Islamic theory and management of education. Epistemologically, knowledge in management of Islamic education is derived more from religious texts and traditions and contemporary education and management theories. As for research significant majority (93.4%) utilized qualitative research methods, with only 6.6% utilizing quantitative approaches. The research sites included schools, madrasas, Islamic boarding schools, universities, and government institutions. Axiologically, this study would focus on the values that underpin the practice of theses that have direct implications for the development of graduate profiles, including; the enhancement of management skills, deeper insights into educational challenges, curriculum innovation and improvement, the formulation of education policies, and the development of leadership competencies.